Fabrication of a Highly Sensitive Hydrazine Electrochemical Sensor Based on Bimetallic Au-Pt Hybrid Nanocomposite onto Modified Electrode - Azadbakht, Azadeh; Abbasi, Amir Reza (Nano-Micro Letters, 2011)
In this research a novel nickel complex was used as electrocatalyst for electrooxidation of hydrazine. A nano-structured nickel-complex was electrodeposited on a bimetallic Au-Pt inorganic-organic hybrid nanocomposite modified electrode. The electrode possesses a three-dimensional (3D) porous network nanoarchitecture, in which the bimetallic Au-Pt NPs serving as metal nanoparticle based microelectrode ensembles are distributed in the matrix of interlaced 3, 3′, 5, 5′-Tetramethylbenzidine (TMB) organic nanofibers (NFs). Surface structure and composition of the sensor was characterized by scanning electron microscopy. Electrocatalytic oxidation of hydrazine on the surface of modified electrode was investigated with cyclic voltammetry method. The results showed that the nickel-complex films displayed excellent electrochemical catalytic activities towards hydrazine oxidation. The hydrodynamic amperometry at rotating modified electrode at constant potential versus reference electrode was used for detection of hydrazine. Under optimized conditions the calibration plots were linear in the concentration range of 0.2–85 μM and detection limit was found to be 0.1 μM. The modified electrode exhibited reproducible behavior and a high level stability during the electrochemical experiments, making it particularly suitable for the analytical purposes.